Kinetics and Mechanistic Studies of Oxidation of Thioglycolic Acid by Manganese(III) - Gandhi, P.K.; Madhava Rao, B. (Asian Journal of Chemistry, 2010)
Kinetic and mechanistic studies of oxidation of thioglycolic acid by manganic pyrophosphate is extensively studied at various temperatures to evaluate the thermodynamic parameters and stability constant of the intermediary complex. Second order rate constants obtained in these investigations are utilised to correlate the effects of [Thioglycolic acid], [manganese(III)], dissociated [H+], total [SO42–], total [P2O74–] and added [manganese(II)]. The mechanism of the reaction involved the formation of a transitory intermediate 1 : 1 cyclic complex and the disproportionation of the complex through a S—H bond cleavage is the rate determining step. The sulphur containing ion-free radicals dimerise to yield disulphide as the end-oxidation product which is a general observation in the oxidation of α-mercapto carboxylic acids by transition metal ions. Various thermodynamic factors such as ΔE#, –ΔH#, ΔF#, ΔS# and frequency factor(A) are calculated.